Exotic accessory minerals in layered chromities of the Campo Formoso complex (Brazil) - Zaccarini, Federica; Garuti, Giorgio; Martin, Robert (Geologica Acta, 2006)
The Campo Formoso stratiform intrusive complex, in Bahia State, Brazil, considered to be of Paleoproterozoic age, consists of a tabular body of ultramafic rocks about 40 km long and 100-1100 m wide. Thick horizons of chromitite are exploited and the deposits are the richest in Brazil. The complex was intruded by the Campo Formoso calc-alkaline batholith, emplaced by the result of the Transamazonian collision-related orogeny. The peridotite was firstly thoroughly serpentinized, then affected by a renewed cycle of hydrothermal alteration as the batholith cooled, leading in the roof zone to emerald mineralization around roof pendants. An even later influx of fluid led to the formation of talc, silica and carbonates, such that the ultramafic rocks were locally converted to listwanite. The chromitite sequences are highly unusual in containing rather exotic minerals, such as monazite-(La), monazite-(Ce), apatite, galena, bismuthinite, antimony, and three unknown minerals of stoichiometry PbSb2, Pb Sb and PbSb4, all associated with the clinochlore. The latter phases may have formed during hydrothermal activity in the system Pb-Sb. The presence of these exotic minerals in chromitite, which makes this occurrence unique in the world, strongly support the hypothesis that the La, Ce, P, Pb, Bi and Sb were metasomatically added to the Campo Formoso chromitite horizons by hydrothermal fluids emanating from the nearby Campo Formoso calc-alkaline batholith as it cooled.